Efektivitas Pendekatan TARL terhadap Hasil Belajar Siswa Melalui Penggunaan LKPD - Faturrosi, Ahmad; Agustina, Lady; Rhomdani, Rohmad Wahid (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effectiveness of the Teaching at the Right Level (TaRL) approach in improving students’ learning outcomes through the use of Student Worksheets (LKPD) in tenth-grade Mathematics at SMK Muhammadiyah 04 Kalisat. The method used was Classroom Action Research (CAR) based on John Elliot’s model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were 27 students. Data were collected through learning outcome tests, observations, and documentation, and analyzed using descriptive quantitative techniques by comparing the mean scores and mastery percentages in each cycle. The results showed that the implementation of the TaRL approach through LKPD significantly improved students’ learning outcomes. The class average score increased from 76.67 in Cycle I to 82.5 in Cycle II, while the mastery level improved from 22.22% to 88.89%. In addition, students’ motivation, participation, and self-confidence during the learning process also increased. In conclusion, the TaRL approach integrated with LKPD is effective in enhancing students’ mathematics learning outcomes and fostering a more active, differentiated, and ability-based learning environment. Keywords: Differentiated learning, Learning outcomes, LKPD, Teaching at the Right Level (TaRL).